The Anglo-Scots Monetary Union of 1707. Issue 3 (September 2019) - Fox, David
Abstract : Article XVI of the Acts of Union of 1706 and 1707 created a monetary union by merging the Scottish monetary system with the sterling monetary system of England and Wales. It completed a process that began after the 1603 regal union between the two kingdoms. Its main purpose was to restore the circulating currency in Scotland and England to the same monetary standard, something which had been an aim of Scottish monetary policy since the early decades of the regal union. The monetary union of 1707 raised difficult numismatic and legal problems in the way prices were quoted, debts were paid and accounts were kept. The monetary events of 1707 illustrate how the legal conception of a monetary union can mean different things in different historical periods. Modern-day legal understandings of monetary union cannot be projected into the past when monetary systems were based on coins struck from intrinsically valuable metals.